Teknologi Informasi Untuk Pengembangan dan Meningkatkan Penjualan Usaha Kecil Menengah di Seruni Sidoarjo - Suparjo, Suparjo; Setyono, Gatot (JHP17 (Jurnal Hasil Penelitian), 2022)
The location ofÂ Shoe Village in Seruni Sidoarjo is a shoe production industry home. As a hometown of shoe production, this area has the potential to be developed into a shoe product center which later became the icon of Sidoarjo.Information Technology is an important part of people's lives. Communities can directly experience the benefits of information directly to recognize the development of the world, including business development. The location of Shoe Village in Seruni Sidoarjo is a shoe production industry home. As a hometown of shoe production, this area has the potential to be developed into a shoe product center which later became the icon of Sidoarjo. Where when tourists go to Sidoarjo then they will visit this village to get a typical Sidoarjo shoes. Production and marketing aspects that have been done so far are still indifidual and traditional. This research wants to develop marketing strategy together with SME Seruni shoes with SWOT analysis method by utilizing information technology. The goal is to increase sales of SMEs through information technology with website address marketingukm.com so that SMEs are expected to grow more and grow, as for some of the results of consumers in online shopping can be increased by the flexibility in making product choices, and delivery on time. Â Keywords : Website, Marketing, SME